Physico-Mechanical Characterization of Hybrid Composite Gasket Developed Using Sugarcane Bagasse Ash, Soda-Lime Waste Glass Powder, and Epoxy Resin - Idowu, E. A.; Adekunle, N. O.; Akinmusire, F. O.; Raji, R. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
The environmental and health risks posed by conventional gasket materials such as asbestos and synthetic rubbers have created a pressing need to develop sustainable alternatives for mechanical sealing applications. This study investigated the potential of hybrid composite gaskets composed of sugarcane bagasse ash, soda-lime waste glass powder, and epoxy resin as an environmentally friendly alternative. Five different compositions were formulated using the hand lay-up method and evaluated for mechanical and thermal properties such as density, porosity, hardness, tensile strength, thermal endurance, Scanning Electron Microscopy (SEM), and X-ray Fluorescence (XRF) analysis. The results showed that Sample C1 (10% bagasse ash, 30% glass powder, 60% epoxy) demonstrated optimal performance, recording the highest tensile strength of 30.91 N/mm² and a thermal resistance of 170oC. These values exceed the typical performance range of NBR (Nitrile Butadiene Rubber) gaskets, which generally show a tensile strength of 17 N/mm² and a thermal resistance range of 120°C. All samples exhibited low porosity (0.01%–0.04%), supporting effective sealing capability, although still higher than the NBR control gasket (0.008%). XRF analysis revealed that SiO2 was the dominant oxide in both fillers, contributing to thermal stability, hardness, and wear resistance, while Al2O3 and CaO enhanced structural rigidity. SEM examination of the optimal sample (Sample C1) revealed that its superior performance was primarily due to regions of uniform filler dispersion and strong interfacial bonding. While high-resolution imaging at 6,000x and 7,000x identified localized micro-voids and filler pull-out, these were isolated instances that did not compromise the structural integrity of the composite. The high tensile strength indicates that the well-bonded regions in the optimal 30:10 (Glass:Ash) ratio effectively dominated the load-transfer mechanism. The presence of micro-voids, visible only at high magnifications, provided the physical basis for the 0.04% porosity without significantly impairing the primary mechanical and thermal performance of the sample.